Experimental design of a novel target to isolate HCV monoclonal antibodies - Brice, Sophie (2014)
Hepatitis C Virus currently affects up to 3% of the world’s population. There is no effective vaccine yet available and the natural immune response to infection is largely inefficient. Progress has been made in isolating several broad-acting neutralizing antibodies that target the viral envelope protein E2. However, a dominant element of the epitopes targeted is an overlap with the highly conserved CD81 binding sites. Various E2 constructs were investigated as possible targets to be used in phage display panning of a combinatorial library of the phagemid vector pComb3H. HVR2 deletion showed optimal exposure of the CD81 binding sites and D535A disrupted known CD81 epitopes. A selection technique was designed to improve exposure of conserved sites on an E2 construct target molecule that disrupts CD81 epitopes while remaining conformationally correct. Optimisation of the screening methodology was used to assess the quality of enrichment of the library panning along with more efficient selection of specific clones. The approach adopted in this project isolated Fab clones specifically reactive to the protein target, one of which also showed preferential binding in acidic environments. Taken together, the information gathered on E2 and the implementation of the phage display method described will contribute to more effective ways of isolating novel antibodies.